Empowerment of the aerospace potential centre in preparing the reserve components of the Indonesian Air Force - Jeffry D Ritiau; Joni Widjayanto; Afrizal Hendra; Sukma Wijaya (Strategi Perang Semesta, 2022)
The aim is to develop the capability to prepare reserve components for the air force in order to double the strength of the Indonesian Air Force in the context of national defense, this is based on the request of the Ministry of Defense to procure 500 personnel of Komcad every year. However, the implementation in the field is still not well organized and correct. This writing is done by using descriptive analysis method that describes the data and facts. Results To support the procurement of Komcad so that it can run well as expected with the Development of Capability for Preparation of Air Force Reserve Components at the Center for Aerospace Potential (Puspotdirga), it is necessary to have a strategy, namely an organizational change strategy and a Puslatpotdirga Development Plan.